2008
DOI: 10.1111/j.1440-1681.2008.04997.x
|View full text |Cite
|
Sign up to set email alerts
|

PANAX NOTOGINSENG SAPONINS ATTENUATE ATHEROSCLEROSIS IN RATS BY REGULATING THE BLOOD LIPID PROFILE AND AN ANTI‐INFLAMMATORY ACTION

Abstract: Previous studies have reported on the anti-atherosclerotic effects of Panax notoginseng saponins (PNS). The aim of the present study was to explore the molecular mechanisms responsible for the anti-atherosclerotic effects of PNS and the inflammatory response. Thirty rats were randomly divided into three groups, namely a control group, a group, in which zymosan A was used to induce inflammation (Zym group) and a PNS-treated group. Rats in the three groups were administered liquid paraffin (i.p.), zymosan A (20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 27 publications
4
56
0
1
Order By: Relevance
“…In accordance with our previous findings in rabbit and rat experiments [9,18], satisfactory anti-atherogenic effect of PNS on apoE -/- mice was observed, displaying decreased size of aortic plaques, reduced ratio of intima-to-media, and alleviation of atherosclerotic pathological changes in arteries. Moreover, the quantitative analysis revealed that PNS treatment was associated with a reduction in intralesional SMCs, particularly in the high-dose PNS-treated mice.…”
Section: Discussionsupporting
confidence: 76%
“…In accordance with our previous findings in rabbit and rat experiments [9,18], satisfactory anti-atherogenic effect of PNS on apoE -/- mice was observed, displaying decreased size of aortic plaques, reduced ratio of intima-to-media, and alleviation of atherosclerotic pathological changes in arteries. Moreover, the quantitative analysis revealed that PNS treatment was associated with a reduction in intralesional SMCs, particularly in the high-dose PNS-treated mice.…”
Section: Discussionsupporting
confidence: 76%
“…A number of studies have shown that different kinds of saponins lower serum cholesterol levels in a variety of animals and human subjects (Southon et al, 1988;Potter et al, 1993;Matsuura, 2001). However, there is no agreement on the specific hypocholesterolemic activity of all saponins and the search for new saponin sources continues (Li et al, 2007;Son et al, 2007;Zhang et al, 2008;Zhao et al, 2008). Recently, we conducted a study to compare different kinds of saponins as a hypocholesterolemic agent in rats.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been fairly well established that ginseng saponin is involved in lipid metabolism in vivo, and it appears to exert some powerful lipid-reduction effects. For example, several reports have asserted that saponin is tightly associated with disease conditions originating in lipid or cholesterol metabolism disorders, including hypertension (Stavro et al, 2005), hyperlipidemia (Wen et al, 1996;Yang et al, 1999), hypercholesterolemia (Lin et al, 1993), and arteriosclerosis (Zhang et al, 2008). Many of the effects of ginseng saponin, such as the suppression of increases in blood cholesterol contents, promotion of cholesterol excretion, prevention of blood vessel lesions caused by hypercholesterolemia, and the amelioration of arteriosclerosis via induced reductions in low-density lipoprotein (LDL) cholesterol and increases in high-density lipoprotein (HDL) cholesterol levels have been continuously elucidated in animal experiments (Yamamoto et al, 1983).…”
Section: Introductionmentioning
confidence: 99%